Development of knowledge base of intellectual system for support of formal and informal training of IT staff - Kurvaeva, L V; Gavrilova, I V; Mahmutova, M V; Chichilanova, S A; Povituhin, S A (Journal of physics. Conference series, 2018)
The choice of educational digital content, according to education goals (descriptors which are formed by competences, labor functions, etc.), becomes an important practical task because of the variety of existing educational online systems that is available to persons within formal, informal IT education formats. Ontologies can form a basis for working out knowledge bases, which are center of intellectual system support in IT specialist training. The paper describes a technology of ontological model creation; analyzes the structure and the content of basic data. The structure of knowledge interrelation of the considered subject and IT education is considered. This knowledge base is applied for solving tasks of educational and methodical supplementation of educational programs of the higher and additional professional education, corporate training; for creating systems of certification and testing for students and practicing experts; for forming individual trajectories of training and career development.